Identification of earthquake-prone areas as a regional planning study for deli serdang regency. Issue 1 (1st February 2022) - Barlian, Edo; Tarigan, Johannes; Nasution, Zulkifli; Purwoko, Agus
Abstract: The main effect of an earthquake for an area is the loss that has an impact on social, economic and physical conditions. Based on earthquake data from the USGS, the earthquake that occurred in the North Sumatra area would have an impact on the surrounding area, especially in Deli Serdang Regency. Seen from the geological map, the Medan sheet shows that the Deli Serdang area is located in a fault zone. The purpose of this study is to identify earthquake-prone areas as a study in regional planning in Deli Serdang Regency with the target of this research being to provide benefits in policy making and readiness for earthquake risk in Deli Serdang Regency and this research will contribute to science in identifying areas that have the potential for earthquake disasters. The method in this study emphasizes data collection in the form of rock types, land slopes, seismic data in the form of soil acceleration in the bedrock and areas located in the fault zone. These parameters will be weighted and analyzed in order to obtain a model that represents field conditions. Analyzing the data using the overlay method so as to obtain the typology of earthquake-prone areas. The results of the analysis describe the typology of earthquake-prone areas consisting of areas with typology A with a stable classification of 10.45%, typology A with a less stable classification of 39.51%, typology B with a less stable classification of 43.89%, typology C with less stable classification was 4.89%, the area with typology D and unstable classification was 1.25% and the area with typology E classification unstable was 0.02%.